Composite nanofiltration membranes, methods of making, and applications thereof in filtering emerging contaminants

CN122912696APending Publication Date: 2026-10-16BAOSHENGTONG (JINGGANGSHAN) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611214722.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,中空结构的纳米纤维在膜分离过程中,水分子传输仍然受到壳层阻力影响

Benefits of technology

[0049]本申请的有益效果在于:在亲水性多孔基膜支撑层上构建取向多孔中空纳米纤维中间层,能够通过中空腔储存水相单体,并通过表面孔结构和壳层结构共同调控水相单体扩散及水分子传输;在界面聚合过程中,该中间层为PIP与TMC反应提供更稳定的反应界面,诱导形成超薄、高交联度且具有规则褶皱结构的聚酰胺过滤皮层,从而在保持较高截留率的同时显著提高水通量,并改善新兴污染物去除、运行稳定性和抗污染性能。本申请的复合纳滤膜及其制备方法,具有操作简单、材料成本低的优点,为水处理领域的复合纳滤膜及其制备提供了性能更优的选择。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912696A_ABST
    Figure CN122912696A_ABST
Patent Text Reader

Abstract

The application provides a composite nanofiltration membrane, a preparation method and application thereof in filtering emerging pollutants. The composite nanofiltration membrane comprises a porous base film support layer, an oriented porous hollow nanofiber intermediate layer and a filtration skin layer, wherein the oriented porous hollow nanofiber intermediate layer is loaded on the porous base film support layer, the nanofiber has a hollow cavity extending along the fiber axis and a pore structure distributed on the surface of the fiber shell layer, and the surface of the filtration skin layer forms a wrinkle structure along the arrangement direction of the nanofiber. By using the oriented porous hollow nanofiber intermediate layer, the water phase monomer storage capacity can be improved and the diffusion behavior can be regulated, so that the interfacial polymerization reaction is carried out under controlled conditions, and an ultrathin, high-crosslinking-degree and regular wrinkle-structure polyamide filtration skin layer is formed, thereby shortening the water molecule transmission path, reducing the permeation resistance, and realizing the synchronous improvement of the membrane permeability and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of water treatment technology, and in particular to a composite nanofiltration membrane, its preparation method, and its application in filtering emerging pollutants. Background Technology

[0002] Currently, the global supply and demand imbalance for freshwater resources is becoming increasingly prominent, and finding stable and sustainable unconventional water sources has become an important way for countries around the world to cope with the water crisis. Thin-film composite nanofiltration (TFC NF) membranes with interlayer structures have attracted widespread attention due to their excellent separation performance in removing emerging pollutants and various small molecules from water bodies.

[0003] However, interlayer nanomaterials, including nanoparticles such as TiO2, carbon nanotubes, and graphene oxide, as well as one-dimensional and two-dimensional nanomaterials, are often limited by challenges such as agglomeration, uneven distribution, and secondary pollution from dissolution and release, which greatly impair the performance and practical feasibility of thin-film composite nanofiltration (TFC NF) membranes.

[0004] In recent years, coaxial electrospinning technology has been applied to membrane separation due to its ability to continuously prepare ultrafine fibers with diameters ranging from nanometers to micrometers. By designing core and shell solution systems, hollow nanofibers can be prepared, further endowing the fibers with internal cavities and providing new ideas for functional modification. However, in the membrane separation process, water molecule transport in hollow nanofibers is still affected by shell resistance. Summary of the Invention

[0005] To address the aforementioned technical problems, this application provides a composite nanofiltration membrane, its preparation method, and its application in filtering emerging pollutants. The composite nanofiltration membrane provided in this application, due to its oriented porous hollow nanofiber interlayer with hollow cavities and surface pores, can store a large amount of amine monomers and regulate the diffusion rate of aqueous monomers. This transforms the interfacial polymerization reaction from rapid, disordered polymerization to a controlled diffusion-dominated mechanism, forming an ultrathin, highly cross-linked filter skin with regular pleats along the fiber arrangement direction of the oriented porous hollow nanofiber interlayer. This effectively shortens the transport path of water molecules, reduces permeation resistance, improves separation performance, and achieves a simultaneous improvement in membrane permeability and selectivity.

[0006] In a first aspect, this application provides a composite nanofiltration membrane, comprising a porous base membrane support layer, an oriented porous hollow nanofiber interlayer, and a filter skin layer. The porous base membrane support layer is composed of a hydrophilic organic material. The oriented porous hollow nanofiber interlayer is loaded on the porous base membrane support layer. The filter skin layer is formed on the porous base membrane support layer on which the oriented porous hollow nanofiber interlayer is loaded. The nanofibers of the oriented porous hollow nanofiber interlayer have hollow cavities and surface pore structures, and the surface of the filter skin layer has a wrinkled structure along the fiber arrangement direction of the oriented porous hollow nanofiber interlayer.

[0007] Preferably, the oriented porous hollow nanofiber intermediate layer is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, and the pore structure is formed by removing the polyvinylpyrrolidone (PVP) component from the electrospinning shell solution.

[0008] Preferably, the porous base membrane support layer is a polyethersulfone (PES) base membrane, and the filter layer is a polyamide (PA) layer.

[0009] Preferably, the thickness of the polyamide layer is 45 nm to 70 nm, more preferably 50 nm to 65 nm.

[0010] The second aspect of this application, as Figure 1 As shown, a method for preparing a composite nanofiltration membrane is provided, comprising the following steps:

[0011] S1. Obtain a hydrophilic porous base membrane support layer;

[0012] S2. An oriented porous hollow nanofiber intermediate layer is prepared by coaxial electrospinning and loaded onto the porous base film support layer to form a composite substrate.

[0013] S3. An interfacial polymerization reaction is carried out on the composite substrate to form a polyamide filter layer.

[0014] Preferably, the porous base membrane support layer obtained in step S1 is a polyethersulfone (PES) base membrane layer, the oriented porous hollow nanofiber intermediate layer prepared by coaxial electrospinning in step S2 is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, the composite substrate is formed by loading the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer on the polyethersulfone (PES) base membrane layer, and the filter skin layer prepared in step S3 is a polyamide (PA) layer.

[0015] Preferably, step S2 includes:

[0016] S21. Prepare an electrospinning shell solution and an electrospinning core solution; wherein the shell solution is prepared by dissolving polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) in a mixed solvent of N,N-dimethylformamide (DMF) and acetone, and the core solution is prepared by dissolving polyvinylpyrrolidone (PVP) in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc);

[0017] S22. The electrospinning shell solution and the electrospinning core solution are simultaneously spun by coaxial electrospinning, and then subjected to ethanol soaking, water bath treatment and drying treatment to obtain an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer with hollow cavity and surface pore structure.

[0018] Preferably, in step S21, the electrospinning solution is prepared by the following steps: polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) powders are completely dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and acetone to prepare an electrospinning shell solution; polyvinylpyrrolidone (PVP) powders are completely dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) to prepare an electrospinning core solution.

[0019] Preferably, the method for preparing the electrospinning shell solution in step S21 includes: dissolving a 15% (w / v) concentration of polyvinylidene fluoride (PVDF) polymer and a 5% to 20% mass percentage of polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:1, completely dissolving at a constant temperature of 60°C, and allowing to stand at 15°C to 25°C for degassing for at least 24 hours; preferably, the mass percentage of polyvinylpyrrolidone (PVP) is 10%.

[0020] Preferably, in step S21, the preparation method of the electrospinning core layer solution includes: dissolving 30% by mass of polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) in a volume ratio of 1:1, completely dissolving it under constant temperature conditions of 60°C, and letting it stand for more than 24 hours.

[0021] Preferably, the coaxial electrospinning method is completed by an electrospinning device. Under the condition of collector rotation, the electrospinning time is set to 5 to 20 minutes, and the electrospinning shell solution and the electrospinning core solution are electrospinned simultaneously.

[0022] Preferably, the conditions for coaxial electrospinning are as follows: applying a voltage of 18 kV, maintaining the ambient relative humidity at 40% RH to 50% RH, setting the collector rotation speed to 700 rpm, the propulsion speed of the electrospinning shell solution to 2.0 mL / h, the propulsion speed of the electrospinning core solution to 1.5 mL / h, and setting the electrospinning duration to 10 minutes.

[0023] Preferably, step S3 includes:

[0024] S31. The composite substrate is immersed in an aqueous solution containing a polyamine compound, and after a first specified time, excess aqueous solution is removed from the side of the composite substrate to which the filter layer is to be formed, to obtain a pretreated membrane.

[0025] S32. Remove excess aqueous solution from the surface of the pretreated membrane and uniformly disperse the aqueous solution on the membrane surface;

[0026] S33. Pour an organic phase solution containing polyacrylamide compounds onto the pretreated membrane and carry out an interfacial polymerization reaction. After a second specified time, remove the excess organic phase solution and dry and cure it to obtain a composite nanofiltration membrane with a polyamide (PA) layer.

[0027] Preferably, step S3 further includes the steps of preparing an aqueous phase solution and an organic phase solution, wherein the aqueous phase solution containing the polyamine compound is a piperazine (PIP) aqueous phase solution, and the organic phase solution containing the polyacrylamide compound is a 1,3,5-benzenetricarboxyl chloride (TMC) organic phase solution; more preferably, the aqueous phase solution is a 0.5 wt% aqueous solution of piperazine (PIP), and the organic phase solution is a 0.1% (w / v) solution of 1,3,5-benzenetricarboxyl chloride (TMC).

[0028] Preferably, the first specified time is 3 to 7 minutes, more preferably 4 minutes and 30 seconds; the second specified time is 1 to 6 minutes, more preferably 2 minutes; after the interface polymerization, it is air-dried for 60 seconds and cured in an oven for 5 minutes.

[0029] Specifically, in a further detailed implementation, such as Figure 2 As shown, the specific preparation method of the composite nanofiltration membrane of this application by coaxial electrospinning includes the following steps:

[0030] S1-1: Pretreatment of polyethersulfone (PES) based film;

[0031] S2-1: Prepare the electrospinning shell layer solution and electrospinning core layer solution required for preparing the intermediate layer of oriented porous hollow polyvinylidene fluoride (PVDF) nanofibers;

[0032] S3-1: Simultaneously perform coaxial electrospinning on the electrospinning shell layer solution and the electrospinning core layer solution to prepare an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, and load it on the polyethersulfone (PES) base film to form a composite substrate.

[0033] S4-1: Place the composite substrate with the side of the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer facing upward on a flat plate, and carry out an interfacial polymerization reaction on this side to obtain a polyamide (PA) layer with selective permeability.

[0034] Preferably, in step S1-1, the polyethersulfone (PES) base film is pretreated, including soaking and neutralization treatment.

[0035] Preferably, step S2-1 includes:

[0036] S2-11. The steps for preparing the electrospinning shell solution are as follows: Dissolve 15% (w / v) polyvinylidene fluoride (PVDF) polymer and 5% to 20% (by mass) polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and acetone at a volume ratio of 3:1. Then, heat the solution to 60°C using a water bath and stir for 10 hours until completely dissolved. After stirring, allow it to stand at room temperature (15°C to 25°C) for degassing for 24 hours to obtain the spinning shell solution for preparing the porous hollow nanofiber intermediate layer; preferably, the mass percentage of polyvinylpyrrolidone (PVP) is 10%.

[0037] S2-12. The steps for preparing the electrospinning core layer solution are as follows: Dissolve 30% (by mass) of polyvinylpyrrolidone (PVP) powder in a solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) in a volume ratio of 1:1. Then, heat the solution to 60°C using a water bath and stir for 10 hours until completely dissolved. After stirring, let the solution stand for 24 hours to obtain the electrospinning core layer solution for preparing the porous hollow nanofiber intermediate layer.

[0038] Preferably, in step S3-1, the electrospinning shell layer solution and the electrospinning core layer solution are poured into two 10 mL syringes, each containing 5 mL. The inner and outer spinning solutions are simultaneously electrospinned for 10 minutes using a screw-type coaxial needle, and deposited onto the surface of a collector coated with a polyethersulfone (PES) substrate film. After spinning, the composite substrate is immersed in anhydrous ethanol for 1 minute, followed by a water bath for 1 hour. After removal, it is dried in a 50°C oven for 4 hours to obtain a PES substrate film with a loaded, oriented, porous, hollow PVDF nanofiber interlayer.

[0039] Preferably, in step S3-1, the coaxial electrospinning conditions are as follows: spinning voltage 18 kV, ambient relative humidity maintained at 40% RH to 50% RH, collector rotation speed 700 rpm, shell solution propulsion speed 2.0 mL / h, core solution propulsion speed 1.5 mL / h, round trip distance fixed at 150 mm, and moving speed 32 mm / s.

[0040] Preferably, the preparation of the polyamide (PA) layer in step S4-1 includes:

[0041] S4-11. Immerse the composite substrate in an aqueous solution, and after complete immersion for a first specified time, pour off the excess aqueous solution and make the aqueous solution on the surface evenly dispersed.

[0042] S4-12. Slowly pour the organic phase solution onto the composite substrate treated in S4-11 to carry out the interfacial polymerization reaction, and remove the excess organic phase solution after the second specified time.

[0043] S4-13. After the membrane treated in S4-12 is air-dried, it is placed in an oven for curing to obtain a composite nanofiltration membrane with a polyamide (PA) layer.

[0044] Preferably, the first specified time is 3 to 7 minutes, more preferably 4 minutes and 30 seconds; the second specified time is 1 to 6 minutes, more preferably 2 minutes; the air drying time is 30 to 90 seconds, more preferably 60 seconds; and the oven curing time is 5 minutes.

[0045] Preferably, the aqueous phase solution is a piperazine (PIP) aqueous phase solution, and the organic phase solution is a 1,3,5-benzenetricarboxylic acid chloride (TMC) organic phase solution.

[0046] Preferably, before step S4-11, the polyethersulfone (PES) base film of the loaded oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber interlayer is placed flat on a clean glass plate and fixed around the edges using a frame and rubber rings.

[0047] A third aspect of this application provides a composite nanofiltration membrane, which is prepared by any of the preparation methods described in the second aspect of this application.

[0048] A fourth aspect of this application provides the use of the composite nanofiltration membrane described in the first or third aspect of this application in filtering or retaining emerging pollutants; said emerging pollutants include at least one pollutant selected from methylparaben (MP), propylparaben (PP), benzylparaben (BP), bisphenol A (BPA), sulfamethoxazole (SMX), trimethoprim (TMP), 2-methylisoborneol (2-MIB), and geosmin (GSM).

[0049] The beneficial effects of this application are as follows: An oriented porous hollow nanofiber interlayer is constructed on a hydrophilic porous base membrane support layer, which can store aqueous monomers through the hollow cavity and regulate the diffusion of aqueous monomers and water molecule transport through the surface pore structure and shell structure. During interfacial polymerization, this interlayer provides a more stable reaction interface for the PIP and TMC reaction, inducing the formation of an ultrathin, highly cross-linked polyamide filter skin with a regularly wrinkled structure. This significantly improves water flux while maintaining a high rejection rate, and enhances the removal of emerging pollutants, operational stability, and antifouling performance. The composite nanofiltration membrane and its preparation method of this application have the advantages of simple operation and low material cost, providing a superior option for composite nanofiltration membranes and their preparation in the field of water treatment. Attached Figure Description

[0050] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0051] Figure 1 This is a schematic diagram of the preparation process of the composite nanofiltration membrane of this application;

[0052] Figure 2 This is a schematic diagram of the preparation process of the composite nanofiltration membrane according to a specific embodiment of this application;

[0053] Figure 3 This is a schematic diagram of the surface morphology of oriented porous hollow nanofibers in the embodiments of this application;

[0054] Figure 4 This is a schematic diagram of the dynamic contact angle of the composite substrate in the comparative examples and embodiments of this application;

[0055] Figure 5 This is a schematic diagram of a scanning electron microscope (SEM) image of the composite nanofiltration membrane surface in the comparative examples and embodiments of this application;

[0056] Figure 6The images show schematic diagrams of the cross-section of the composite nanofiltration membrane obtained by scanning electron microscopy (SEM) and atomic force microscopy (AFM) for comparative examples and embodiments of this application.

[0057] Figure 7a This is a schematic diagram of the water contact angle (WCA) of the composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0058] Figure 7b This is a schematic diagram of the Zeta potential of the composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0059] Figure 8a These are schematic diagrams of the Fourier transform infrared (FTIR) spectra of the composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0060] Figure 8b Schematic diagrams of X-ray photoelectron spectroscopy (XPS) of composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0061] Figure 9 Schematic diagrams showing the pure water flux and Na2SO4 salt retention effect of composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0062] Figure 10a , 10b Schematic diagrams of polyethylene glycol (PEG) retention and pore size distribution curves of composite nanofiltration membranes in different comparative examples and embodiments of this application;

[0063] Figure 11a , 11b This is a schematic diagram showing the permeation flux and retention performance of the composite nanofiltration membrane for different salts in the comparative examples and embodiments of this application;

[0064] Figure 12a , 12b This is a schematic diagram illustrating the preparation principle of the composite nanofiltration membrane in the comparative examples and preferred embodiments of this application;

[0065] Figure 13a , 13b This is a schematic diagram illustrating the removal effect of the composite nanofiltration membrane on emerging pollutants in the comparative examples and embodiments of this application;

[0066] Figures 14a-14c This is a schematic diagram illustrating the operational stability of the composite nanofiltration membrane according to a preferred embodiment of this application.

[0067] Figure 15a , 15b This is a schematic diagram illustrating the antifouling performance of the composite nanofiltration membrane according to a preferred embodiment of this application;

[0068] Figure 16 This is a schematic diagram comparing the performance of the composite nanofiltration membrane of the preferred embodiment of this application with other composite nanofiltration membranes. Detailed Implementation

[0069] To make the technical means, creative features, objectives and effects of this application easier to understand, the following description, in conjunction with specific illustrations, further elaborates on this application.

[0070] One aspect of this application provides a composite nanofiltration membrane, comprising a porous base membrane support layer, an oriented porous hollow nanofiber interlayer, and a filter skin layer; the porous base membrane support layer is composed of a hydrophilic organic material, the oriented porous hollow nanofiber interlayer is loaded on the porous base membrane support layer, and the filter skin layer is formed on the porous base membrane support layer loaded with the oriented porous hollow nanofiber interlayer; the nanofibers of the oriented porous hollow nanofiber interlayer have hollow cavities and surface pore structures, and the surface of the filter skin layer has a wrinkled structure along the fiber arrangement direction of the oriented porous hollow nanofiber interlayer.

[0071] In one specific embodiment, the oriented porous hollow nanofiber interlayer is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber interlayer. The pore structure is formed by removing the polyvinylpyrrolidone (PVP) component from the electrospinning shell solution. The porous base membrane support layer is a polyethersulfone (PES) base membrane, and the filter skin layer is a polyamide (PA) layer. Further, the polyamide layer is an ultrathin layer with a thickness of 45 nm to 70 nm, a crosslinking degree of 62.01% to 75.23%, and a water contact angle of 25.7° to 51.7°. In a preferred embodiment, the water flux can reach 28.52 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate can reach 97.61%.

[0072] In this embodiment, the polyethersulfone (PES) base film is a porous substrate. After depositing an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber interlayer, the macroporous structure on the surface of the PES base film is gradually covered by the nanofibers, changing the hydrophilicity while the pore size of the substrate remains essentially unchanged, forming a new substrate morphology. The hollow cavity and surface pore structure of the oriented porous hollow PVDF nanofiber interlayer can store aqueous monomers and regulate their release, while providing additional transport channels for water molecules; thus, the polyamide (PA) layer formed by interfacial polymerization has a thinner thickness, higher crosslinking degree, and a wrinkled structure distributed along the fiber direction, which can achieve high water flux while maintaining good retention effect.

[0073] Another aspect of this application provides the application of the aforementioned composite nanofiltration membrane in filtering or retaining emerging pollutants, said emerging pollutants including at least one pollutant selected from methylparaben (MP), propylparaben (PP), benzylparaben (BP), bisphenol A (BPA), sulfamethoxazole (SMX), trimethoprim (TMP), 2-methylisoborneol (2-MIB), and geosmin (GSM).

[0074] This application also provides a method for preparing a composite nanofiltration membrane, such as... Figure 1 As shown, it includes the following steps:

[0075] S1. Obtain a hydrophilic porous base membrane support layer;

[0076] S2. An oriented porous hollow nanofiber intermediate layer is prepared by coaxial electrospinning and loaded onto a porous base film support layer to form a composite substrate.

[0077] S3. Perform interfacial polymerization on the composite substrate to prepare the filter skin.

[0078] In a specific embodiment, the porous base membrane support layer obtained in step S1 is a polyethersulfone (PES) base membrane layer, the oriented porous hollow nanofiber intermediate layer prepared by coaxial electrospinning in step S2 is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, the composite substrate is composed of the oriented porous hollow PVDF nanofiber intermediate layer loaded on the PES base membrane layer, and the filter skin layer prepared in step S3 is a polyamide (PA) layer.

[0079] Further, step S2 includes: S21, preparing an electrospinning shell solution and a core solution, wherein the shell solution contains a mixed solvent of polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), N,N-dimethylformamide (DMF), and acetone, and the core solution contains a mixed solvent of polyvinylpyrrolidone (PVP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc); S22, simultaneously spinning the shell solution and the core solution by coaxial electrospinning to obtain an oriented porous hollow PVDF nanofiber intermediate layer loaded on a polyethersulfone (PES) base film layer; and removing at least some of the PVP by ethanol immersion, water bath, and drying treatment to form a surface porous structure and a hollow cavity.

[0080] In step S21, the electrospinning solution is prepared by the following steps: a certain mass-volume percentage of polyvinylidene fluoride (PVDF) and a certain mass-volume percentage of polyvinylpyrrolidone (PVP) are completely dissolved in a certain volume ratio of a mixed solvent of N,N-dimethylformamide (DMF) and acetone to prepare an electrospinning shell solution; a certain mass-volume percentage of polyvinylpyrrolidone (PVP) powder is completely dissolved in a certain volume ratio of a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) to prepare an electrospinning core solution. In this application, the electrospinning shell layer solution preferably consists of 15% (w / v) polyvinylidene fluoride (PVDF) polymer and 5% to 20% (w / v) polyvinylpyrrolidone (PVP) powder dissolved in a 3:1 volume ratio of N,N-dimethylformamide (DMF) and acetone, stirred at 60°C for 10 hours until completely dissolved, and then allowed to stand at 15°C to 25°C for at least 24 hours to degas; the electrospinning core layer solution preferably consists of 30% (w / v) polyvinylpyrrolidone (PVP) powder dissolved in a 1:1 volume ratio of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) solution, stirred at 60°C for 10 hours until completely dissolved, and then allowed to stand for at least 24 hours.

[0081] Electrospinning is performed using an electrospinning apparatus. At a specific rotation speed, the electrospinning time is set to 5 to 20 minutes, simultaneously performing coaxial electrospinning on the shell and core solutions. Preferred electrospinning conditions in this application are: an applied voltage of 18 kV, an ambient relative humidity maintained at 40% RH to 50% RH, a collector rotation speed of 700 rpm, a shell solution feed rate of 2.0 mL / h, a core solution feed rate of 1.5 mL / h, and a spinning time of 10 minutes.

[0082] Step S3 includes: S31, immersing the composite substrate in an aqueous solution containing a polyamine compound, and removing excess aqueous solution after a first specified time, such as 3 to 7 minutes, to obtain a pretreated membrane; S32, performing surface treatment on the pretreated membrane; S33, pouring an organic solution containing a polyacrylamide compound onto the pretreated membrane to carry out an interfacial polymerization reaction, and removing excess organic solution after a second specified time, such as 1 to 6 minutes, to obtain a composite nanofiltration membrane with a polyamide (PA) layer. In this application, the aqueous solution is a piperazine (PIP) aqueous solution, and the organic solution is a 1,3,5-benzenetricarboxylic acid chloride (TMC) organic solution.

[0083] In a further embodiment, a composite nanofiltration membrane is prepared by coaxial electrospinning, wherein the porous base membrane support layer is a polyethersulfone (PES) base membrane layer, the oriented porous hollow nanofiber intermediate layer is an oriented porous hollow PVDF nanofiber intermediate layer, and the filter skin layer is a polyamide (PA) layer. Figure 2 As shown, the specific preparation method includes the following steps:

[0084] S1-1: Pretreatment of polyethersulfone (PES) based film;

[0085] S2-1: Prepare the electrospinning shell layer solution and electrospinning core layer solution required for preparing the intermediate layer of oriented porous hollow polyvinylidene fluoride (PVDF) nanofibers;

[0086] S3-1: Simultaneous coaxial electrospinning of the electrospinning shell layer solution and the electrospinning core layer solution to prepare an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, which is then loaded onto a polyethersulfone (PES) base film to form a composite substrate.

[0087] S4-1: Place the composite substrate with one side of the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer facing upward on a flat plate, and carry out an interfacial polymerization reaction on that side to obtain a polyamide (PA) layer with selective permeability.

[0088] Specifically, in step S1-1, the polyethersulfone (PES) base film is pretreated, including: cutting it to a suitable size, which is 15 cm × 15 cm in this embodiment, fixing it on yellow release paper, soaking it, and performing a neutral treatment.

[0089] Step S2-1 includes: S2-11, the steps for preparing the electrospinning shell solution are as follows: a 15% (w / v) concentration of polyvinylidene fluoride (PVDF) polymer and a certain mass percentage of polyvinylpyrrolidone (PVP) powder are dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:1. Then, the mixture is heated to 60°C in a water bath and stirred for 10 hours until completely dissolved. After stirring, the mixture is allowed to stand at room temperature (15°C to 25°C) for 24 hours to degas, thereby obtaining the electrospinning shell solution for preparing the porous hollow nanofiber intermediate layer. S2-12. The steps for preparing the electrospinning core layer solution are as follows: Dissolve 30% by mass of polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) in a volume ratio of 1:1. Then, heat the solution to 60°C in a water bath and stir for 10 hours until completely dissolved. After stirring, let it stand for 24 hours to obtain the electrospinning core layer solution for preparing the porous hollow nanofiber intermediate layer.

[0090] In step S3-1, 5 mL of the electrospinning shell solution and 5 mL of the electrospinning core solution are poured into two 10 mL syringes respectively. The electrospinning shell solution and the electrospinning core solution are simultaneously electrospinned using a screw-type coaxial needle and loaded onto a polyethersulfone (PES) substrate. After electrospinning, the PES substrate with the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer is immersed in anhydrous ethanol solution for 1 minute, followed by a 1-hour water bath and drying to obtain the composite substrate. The preferred electrospinning conditions are: spinning voltage 18 kV, ambient relative humidity maintained at 40% RH to 50% RH, collector rotation speed 700 rpm, shell solution feed rate 2.0 mL / h, core solution feed rate 1.5 mL / h, round trip distance fixed at 150 mm, and moving speed 32 mm / s.

[0091] Before step S4-11, place the composite substrate flat on a clean glass plate and fix it around the edges using a frame and rubber rings.

[0092] In this embodiment, an aqueous solution and an organic solution were prepared by using water as a solvent to prepare a 0.5 wt% piperazine (PIP) aqueous solution in a brown bottle; and a 0.1% (w / v) 1,3,5-benzenetricarboxylic acid (TMC) organic solution was prepared in a brown bottle by using n-hexane as a solvent.

[0093] The preparation of the polyamide (PA) layer in step S4-1 includes: S4-11, pouring piperazine (PIP) aqueous solution into the frame to ensure that the polyethersulfone (PES) base film supporting the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber interlayer is immersed in the piperazine (PIP) aqueous solution for 3 to 7 minutes, preferably 4 minutes and 30 seconds, then pouring off the excess aqueous solution, and using a rubber collection roller to uniformly disperse the piperazine (PIP) aqueous solution on the surface; S4-12, ... A 1,3,5-benzenetricarboxylic acid chloride (TMC) organic phase solution is slowly poured onto the composite substrate treated in S4-11 to carry out an interfacial polymerization reaction for 1 to 6 minutes, preferably 2 minutes. Afterward, excess 1,3,5-benzenetricarboxylic acid chloride (TMC) organic phase solution is removed. In S4-13, the membrane treated in S4-12 is air-dried for 30 to 90 seconds, preferably 60 seconds, and then cured in an oven for 5 minutes to obtain a composite nanofiltration membrane with a polyamide (PA) layer. After preparation, the composite nanofiltration membrane can be stored in deionized water at 4°C.

[0094] To further illustrate the impact of the preparation method of this application on the composite nanofiltration membrane, this application uses the above-described preparation method to conduct different comparative examples and embodiments. In the comparative examples and embodiments, the polyethersulfone (PES) base membrane is labeled as PES; the composite substrates obtained by preparing the electrospinning shell solution using 0% by mass of polyvinylpyrrolidone (PVP) and electrospinning times of 0 min and 10 min are labeled as PES and PES-OH, respectively, and the composite nanofiltration membranes prepared by the interfacial polymerization process are labeled as TFC and TFC-OH, respectively; the composite substrates obtained by preparing the electrospinning shell solution using 5%, 10%, and 20% by mass of polyvinylpyrrolidone (PVP) and electrospinning time of 10 min are labeled as PES-O-P1, PES-O-P2, and PES-O-P3, respectively, and the composite nanofiltration membranes prepared by the interfacial polymerization process are labeled as TFC-O-P1, TFC-O-P2, and TFC-O-P3, respectively.

[0095] The preparation steps of Comparative Example 1 of this application include: Comparative Example 1 is a blank composite nanofiltration membrane without a nanofiber interlayer, which is prepared by direct interfacial polymerization reaction of polyether sulfone (PES) base membrane, and the resulting composite nanofiltration membrane is labeled as TFC.

[0096] 1. Cut the polyethersulfone (PES) base film to a size of 15 cm × 15 cm and fix it on yellow release paper for later use.

[0097] 2. Preparation of electrospinning shell solution: Dissolve 15% (w / v) polyvinylidene fluoride (PVDF) polymer and 0% (w / v) polyvinylpyrrolidone (PVP) powder in N,N-dimethylformamide (DMF) and acetone solvent at a volume ratio of 3:1. Then heat to 60°C in a water bath and stir for 10 hours until completely dissolved. After stirring, let stand at room temperature (15°C to 25°C) for 24 hours to degas, and obtain the electrospinning shell solution.

[0098] The steps for preparing the electrospinning core layer solution are as follows: Dissolve 30% by mass of polyvinylpyrrolidone (PVP) powder in N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) solvents in a volume ratio of 1:1, then heat to 60°C in a water bath and stir for 10 hours until completely dissolved. After stirring, let stand for 24 hours to obtain the electrospinning core layer solution.

[0099] 3. The electrospinning shell solution and the electrospinning core solution were poured into two 10 mL syringes, each containing 5 mL. A spinning voltage of 18 kV was applied, and the relative humidity of the environment was maintained at 40% RH to 50% RH. The spinning speed was set to 700 rpm, the propulsion speed of the spinning shell solution was 2.0 mL·h⁻¹, and the propulsion speed of the spinning core solution was 1.5 mL·h⁻¹. The round-trip distance was fixed at 150 mm, the moving speed was 32 mm·s⁻¹, and the electrospinning time was 0 min. No nanofiber intermediate layer was formed on the surface of the collector wrapped with polyethersulfone (PES) base film. Subsequently, the polyethersulfone (PES) base film was immersed in anhydrous ethanol solution for 1 min, water bath for 1 hour, and then placed in a 50℃ oven to dry for 4 hours to obtain a substrate without a nanofiber intermediate layer.

[0100] 4. Dissolve piperazine (PIP) at a concentration of 0.5 wt% in 50 mL of deionized water in a brown bottle and sonicate for 30 min to obtain an aqueous solution of piperazine (PIP); dissolve 1,3,5-benzenetricarboxylic chloride (TMC) at a concentration of 0.1% (w / v) in 50 mL of n-hexane solvent and sonicate for 30 min to completely dissolve it to obtain an organic solution of 1,3,5-benzenetricarboxylic chloride (TMC).

[0101] The prepared composite substrate is placed flat on a clean glass plate and fixed and leak-proof using a stainless steel frame and rubber ring, with the side of the substrate to be formed into a filter layer facing upwards on the glass plate.

[0102] Pour 50 mL of the prepared piperazine (PIP) aqueous solution into the frame, soak the PES base membrane for 4 minutes and 30 seconds, then pour off the excess aqueous solution, remove the stainless steel frame and rubber ring to obtain the pretreated membrane.

[0103] The membrane surface was pretreated by rolling with a rubber roller. 50 mL of the prepared 1,3,5-benzenetricarboxylic acid chloride (TMC) organic phase solution was poured into the frame and reacted for 2 minutes. After that, the excess organic phase solution was poured off. After air drying for 60 seconds, it was placed in an oven to cure for 5 minutes to obtain a composite nanofiltration membrane with a selectively permeable polyamide (PA) layer.

[0104] The composite nanofiltration membrane prepared above was stored in deionized water at 4°C.

[0105] The composite nanofiltration membrane prepared in Comparative Example 1 is labeled as TFC. The polyamide (PA) layer thickness was difficult to quantify precisely due to defects. The crosslinking degree was 62.01%, the water contact angle was about 51.7°, the water flux was 10.37 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate was 97.02%.

[0106] Comparative Example 2: When preparing the electrospinning shell solution, Comparative Example 2 still used 0% polyvinylpyrrolidone (PVP) by mass. The difference from Comparative Example 1 is that the electrospinning time was 10 min, that is, the spinning time for loading the hollow nanofiber intermediate layer on the polyethersulfone (PES) base film was 10 min. Other conditions were the same as those in Comparative Example 1.

[0107] The composite nanofiltration membrane prepared in Comparative Example 2 was labeled as TFC-OH. The polyamide (PA) layer thickness was 57.6 nm, the degree of crosslinking was 70.27%, the water contact angle was about 36.2°, the water flux was 25.41 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate was 97.69%.

[0108] Example 1: The difference between Example 1 and Comparative Example 2 is that when preparing the electrospinning shell solution, 5% by mass of polyvinylpyrrolidone (PVP) was used, and the electrospinning time was 10 min, that is, the spinning time for loading the oriented porous hollow nanofiber intermediate layer on the polyethersulfone (PES) base film was 10 min. Other conditions were the same as those in Comparative Example 2.

[0109] The composite nanofiltration membrane prepared in Example 1 is labeled TFC-O-P1. The polyamide (PA) layer thickness is 50.2 nm, the degree of crosslinking is 71.49%, the water contact angle is about 33.6°, the water flux is 26.77 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate is 96.95%.

[0110] Example 2: The difference between Example 2 and Comparative Example 2 is that when preparing the electrospinning shell solution, 10% polyvinylpyrrolidone (PVP) by mass was used, and the electrospinning time was 10 min, that is, the spinning time for loading the oriented porous hollow nanofiber intermediate layer on the polyethersulfone (PES) base film was 10 min. Other conditions were the same as those in Comparative Example 2.

[0111] The composite nanofiltration membrane prepared in Example 2 is labeled TFC-O-P2. The polyamide (PA) layer thickness is 50 nm, the degree of crosslinking is 75.23%, the water contact angle is about 26.2°, the water flux is 28.52 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate is 97.61%.

[0112] Example 3: The difference between Example 3 and Comparative Example 2 is that when preparing the electrospinning shell solution, 20% by mass of polyvinylpyrrolidone (PVP) was used, and the electrospinning time was 10 min, that is, the spinning time for loading the oriented porous hollow nanofiber intermediate layer on the polyethersulfone (PES) base film was 10 min. Other conditions were the same as those in Comparative Example 2.

[0113] The composite nanofiltration membrane prepared in Example 3 is labeled TFC-O-P3. The polyamide (PA) layer thickness is 63.75 nm, the degree of crosslinking is 73.97%, the water contact angle is about 25.7°, the water flux is 27.71 L·m⁻²·h⁻¹·bar⁻¹, and the Na₂SO₄ rejection rate is 97.31%.

[0114] As can be seen from the comparative examples and embodiments above, this application uses coaxial electrospinning technology to prepare composite nanofiltration membranes. By optimizing the concentration of polyvinylpyrrolidone (PVP) in the shell spinning solution, the pore structure and hollow cavity structure of the nanofiber surface are controlled, and it is used as an intermediate layer in the preparation of composite nanofiltration membranes. After constructing an oriented porous hollow nanofiber intermediate layer on the polyethersulfone (PES) base membrane layer, the physicochemical properties such as hydrophilicity and roughness of the base membrane surface are changed, which further affects the morphology and performance of the polyamide (PA) layer. The moderate hydrophilicity, mild reaction interface, and controllable monomer diffusion provide a stable reaction environment for the interfacial polymerization of PIP aqueous solution and TMC organic solution, thereby forming a polyamide filter skin with high crosslinking degree and excellent separation performance.

[0115] To better illustrate the process, this application analyzed the morphology, physicochemical properties, and separation performance of different composite nanofiltration membranes using scanning electron microscopy (SEM), atomic force microscopy (AFM), and Fourier transform infrared spectroscopy (FTIR), and evaluated their removal efficiency for emerging pollutants. Compared with TFC and TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3 showed increased crosslinking degree, decreased water contact angle, and significantly improved water flux. The results indicate that, under the optimal condition of 10% PVP mass percentage in the shell solution, the prepared TFC-O-P2 membrane exhibits the best overall separation performance, with a water flux of 28.52 L·m⁻²·h⁻¹·bar⁻¹ and a Na₂SO₄ rejection rate of 97.61%, while maintaining good retention of emerging pollutants.

[0116] Different mass percentages of polyvinylpyrrolidone (PVP) powder are used in the electrospinning process, such as... Figure 3As shown in the figure, a, b, and c represent the surface morphologies of porous hollow polyvinylidene fluoride (PVDF) nanofibers obtained after PVP removal treatment under conditions of 5 wt%, 10 wt%, and 20 wt% polyvinylidene fluoride (PVP) content, respectively. Figure 3 As can be seen, the concentration of polyvinylpyrrolidone (PVP) has a significant regulatory effect on the pore structure of the fiber surface. When the PVP content in the shell solution is 5 wt%, as shown in Figure a, only a small number of dispersed and small-sized pores appear on the surface of the porous hollow nanofibers. When the PVP content increases to 10 wt%, as shown in Figure b, the number of pores on the surface of the porous hollow nanofibers increases significantly, the pore size increases, and the inter-pore connectivity is enhanced, presenting a more open and uniform porous surface structure. When the PVP content is further increased to 20 wt%, as shown in Figure c, the fiber still has a porous structure, but the overall morphology shows obvious distortion, breakage, and discontinuity. This may be because the excessively high PVP content forms an over-porous structure after removal, weakening the supporting role of the polyvinylidene fluoride (PVDF) fiber skeleton. Therefore, a PVP addition of 10 wt% is the preferred condition that balances surface pore structure and fiber integrity.

[0117] Hydrophilicity is a crucial characteristic of the interlayer in porous hollow nanofibers, directly affecting the retention capacity of aqueous monomers and the interfacial polymerization rate. Furthermore, the hydrophilicity of the polyethersulfone (PES)-based film with an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber interlayer was evaluated using dynamic contact angle (DCA) measurements. Figure 4 As shown, the dynamic contact angle decreases over time and eventually approaches 0°. This change is attributed to the fact that the porous structure on the surface of the hollow nanofibers reduces the mass transfer resistance during water molecule transport and allows water molecules to flow rapidly within the fiber channels; at the same time, the capillary action of the internal hollow cavity further accelerates water molecule transport.

[0118] Surface morphology typically affects the separation performance of nanofiltration membranes. To further illustrate the influence of different porous hollow nanofiber interlayers on the morphology of the polyamide (PA) layer, the surfaces of different composite nanofiltration membranes were characterized using scanning electron microscopy (SEM). The results are as follows: Figure 5As shown in Figure a, on the surface of the TFC membrane, due to unconstrained polymerization, the polyamide (PA) layer molecular chains randomly nucleate, grow, and aggregate, ultimately forming a polyamide layer with poor uniformity and low effective specific surface area. After introducing a hollow nanofiber interlayer, as shown in Figure b, in the TFC-OH membrane, the inhibition of the diffusion rate of the aqueous piperazine (PIP) monomer causes the polyamide (PA) layer to generate biomimetic structural wrinkles resembling centipedes along both sides of the fibers. After optimizing the surface pore structure of the porous hollow nanofiber interlayer, as shown in Figures c, d, and e, the prepared TFC-O-P1, TFC-O-P2, and TFC-O-P3 membranes show an further increase in surface wrinkles. This may be attributed to the weakened inhibition of the aqueous monomer by the porous fibers compared to the hollow nanofiber interlayer, leading to increased interfacial instability during the interfacial polymerization reaction and thus generating more wrinkled structures. However, due to the unstable deformation of the intermediate fiber structure, the orderly diffusion of monomers in the TFC-O-P3 membrane is disrupted, and the polyamide (PA) layer molecular chains undergo excessive aggregation, resulting in a reduction in surface wrinkleness.

[0119] Figure 6 The thickness characteristics of the polyamide (PA) layer in different composite nanofiltration membranes are shown in Figures a and a1. As shown in Figures a and a1, the polyamide (PA) layer in TFC exhibits an irregular thickness distribution accompanied by local structural collapse, making precise thickness quantification difficult. After introducing a nanofiber interlayer, as shown in Figures b and b1, the intrusion and collapse of the polyamide (PA) layer in the TFC-OH membrane are significantly alleviated. As shown in Figures b and b1, c and c1, d and d1, e and e1, in TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3, the cross-section of the polyamide (PA) layer is a continuous and complete ultrathin polyamide layer with thicknesses of 57.6 nm, 50.2 nm, 50 nm, and 63.75 nm, respectively. This result indicates that the oriented nanofiber interlayer prepared in this application regulates the interfacial polymerization reaction rate, thereby inhibiting the diffusion rate of piperazine (PIP) monomers during interfacial polymerization, resulting in a thinner polyamide (PA) layer. Among them, TFC-O-P2 has the thinnest polyamide (PA) layer, indicating that the modification condition has the best effect on the regulation of interfacial polymerization. Its regulation of monomer diffusion rate and storage of aqueous solution are more conducive to achieving ultra-thin polyamide (PA) layer thickness.

[0120] Figure 6The AFM images in the figure show the corresponding three-dimensional morphology results obtained through atomic force microscopy (AFM). From the images, it can be seen that the TFC film surface has no obvious undulations and low roughness. However, the surface morphology of the TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3 films shows significant changes, with significant differences in surface peaks and valleys, and a substantial increase in roughness. Combined with… Figure 5 It is evident that a significant increase in membrane surface roughness can substantially increase the effective filtration area of ​​the membrane, providing more active sites and transport channels for water molecule transmembrane transport, which is a crucial structural reason for the improved permeate flux. The introduction of an oriented porous hollow nanofiber interlayer, through precise control of the interfacial polymerization process, successfully prepared a composite nanofiltration membrane with a complete ultrathin polyamide layer, high surface roughness, and a uniform and stable structure. The ultrathin design and the large effective filtration area resulting from the high roughness lay a solid structural foundation for improved membrane separation performance and provide theoretical support at the microstructural level for subsequent antifouling performance and operational stability testing.

[0121] The hydrophilic / hydrophobic properties and charge of the membrane surface are physicochemical factors that determine the membrane's water permeability, antifouling ability, and separation and retention characteristics. The surface hydrophilicity and charge of the composite membrane before and after modification were systematically characterized using water contact angle (WCA) and Zeta potential measurements. Figure 7a In the study, the water contact angle (WCA) of the TFC membrane was 51.7°, while the WCAs of the TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3 membranes decreased to 36.2°, 33.6°, 26.2°, and 25.7°, respectively. This result indicates that the oriented nanofiber interlayer and the induced wrinkled polyamide layer jointly improve the wettability of the membrane surface. Figure 6 The characterization results showed that the surface roughness of the modified film was significantly improved. According to the Wenzel wetting model, increased roughness can further enhance the hydrophilicity effect. Figure 7b It can be observed that the Zeta potential of each nanofiltration membrane decreases with increasing pH value; compared with TFC membrane, the surface negative charge of TFC-OH, TFC-O-P1, TFC-O-P2 and TFC-O-P3 membranes is enhanced, which is beneficial to improve the retention of divalent anions through the Donnan effect.

[0122] To quantitatively analyze the elemental composition and crosslinking degree of the membrane surface, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were performed on the composite membrane, as detailed in Figure 8 and Table 1. The XPS full spectrum shows that the nanofiltration membranes generated in the comparative examples and embodiments of this application all contain characteristic peaks for C, N, and O elements, with binding energies of approximately 284.8 eV (C1s), 399.5 eV (N1s), and 532.0 eV (O1s), respectively, matching the elemental composition of the polyamide composite membrane. The O / N ratio of the TFC membrane was 1.29, while that of the TFC-O-P2 membrane decreased to 1.18. Since the O / N ratio is negatively correlated with the crosslinking degree of the polyamide layer, this indicates that the TFC-O-P2 membrane has a higher degree of crosslinking.

[0123] Table 1. XPS elemental analysis and crosslinking degree of different composite nanofiltration membranes

[0124]

[0125] Permeation flux and solute rejection rate are two core indicators for evaluating the separation performance of nanofiltration membranes, and the trade-off between the two is a key bottleneck restricting the engineering application of traditional polyamide composite membranes. Figure 9 This is a schematic diagram showing the pure water flux and Na2SO4 salt retention effect of the composite nanofiltration membrane in the comparative examples and embodiments of this application. Figure 9 In the comparison, the water permeation flux of the TFC membrane was only 10.4 L·m⁻²·h⁻¹·bar⁻¹; the water permeation flux of the TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3 membranes were all significantly improved. Among them, the flux of the TFC-O-P2 membrane reached 28.5 L·m⁻²·h⁻¹·bar⁻¹, an increase of approximately 176.7% compared to the TFC membrane. The improvement in water permeation flux can be attributed to: 1) increased hydrophilicity of the membrane surface, reducing the resistance to water molecule transport across the membrane interface; 2) the ultrathin polyamide (PA) layer shortening the mass transfer path of water molecules across the membrane; 3) the wrinkled structure increasing the effective filtration area; and 4) the porous structure and hollow cavity of the porous hollow nanofiber intermediate layer providing additional channels for water molecule transport.

[0126] To investigate the effect of the intermediate layer on pore size distribution, neutral polyethylene glycol (PEG) with different relative molecular masses (200, 400, 600, 800, and 1000 Da) was used as the feed liquid, and different nanofiltration membranes were tested using a cross-flow apparatus. Figure 10a , 10bAs shown, the shift in the membrane rejection curve is basically consistent with the change in crosslinking degree. The probability density distribution curve obtained from the rejection curve indicates that the effective pore size of the TFC-O-P2 membrane shifts slightly towards smaller pore sizes, and the pore size distribution also tends to be concentrated. This result indicates that the increased crosslinking degree of the TFC-O-P2 membrane enhances its solute sieving effect. This is because the hollow cavity and surface pore structure of the porous hollow nanofibers are conducive to storing PIP monomers and regulating their release, thereby controlling the interfacial reaction rate and forming a dense and uniform polyamide (PA) layer.

[0127] Figure 11 shows the separation performance test results of the composite nanofiltration membranes of the comparative examples and embodiments of this application for four typical inorganic salts, including Na2SO4, MgSO4, MgCl2, and NaCl, with a feed concentration of 1000 mg / L. Overall, the TFC membrane, along with TFC-OH, TFC-O-P1, TFC-O-P2, and TFC-O-P3 membranes, exhibits typical separation characteristics of negatively charged nanofiltration membranes: the salt solution permeation flux increases in the order Na2SO4 < MgSO4 < MgCl2 < NaCl, while the retention rate for inorganic salts decreases in the order Na2SO4 > MgSO4 > MgCl2 > NaCl. The above membranes show excellent retention performance for the divalent anionic sulfates Na2SO4 and MgSO4, with retention rates exceeding 96%; however, the retention effect for the monovalent anionic chlorides MgCl2 and NaCl is relatively low. This separation behavior is the result of the synergistic effect of the Donnan electrostatic repulsion effect and the size sieving effect.

[0128] To better understand the influence mechanism of the porous hollow nanofiber interlayer on membrane formation, this application uses a conceptual model to explain the performance enhancement mechanism of the TFC-O-P2 membrane, such as... Figure 12a , 12b As shown. Figure 12a In traditional interfacial polymerization processes, piperazine (PIP) monomers diffuse randomly at the reaction interface, which can easily lead to the formation of nodular structures and uneven pores in the polyamide (PA) layer. Figure 12b In this study, the introduction of a porous hollow nanofiber interlayer regulates the diffusion behavior of piperazine (PIP) monomers in the aqueous phase through its hollow cavity and surface pore structure. The fiber surface pore structure induces the aqueous solution to enter and enrich piperazine (PIP) molecules, forming a monomer supply space for the interfacial polymerization reaction. Simultaneously, the fiber shell restricts the free diffusion of the aqueous phase, reducing the overall diffusion rate of piperazine (PIP) and transforming the reaction from traditional rapid, disordered polymerization to a controlled diffusion-dominated mechanism. This regulatory effect induces the formation of an ultrathin, highly cross-linked polyamide (PA) separation layer with a regularly wrinkled structure, effectively shortening the water molecule transport path and reducing permeation resistance.

[0129] like Figure 13aAs shown, the TFC-O-P2 membrane achieved removal rates of 37.47%, 41.34%, 97.03%, and 88.32% for neutral hydrophobic pollutants methylparaben (MP), propylparaben (PP), benzylparaben (BP), and bisphenol A (BPA), respectively; and removal rates of 84.35% and 90.21% for charged pollutants sulfamethoxazole (SMX) and trimethoprim (TMP), respectively. Compared with the TFC membrane, the TFC-O-P2 membrane showed improved removal rates for all of these emerging pollutants. This improvement is mainly attributed to the higher degree of cross-linking, smaller effective pore size, stronger negative charge, and better hydrophilicity induced by the porous hollow nanofiber interlayer; for neutral pollutants, size sieving and hydrophobic interactions played a combined role; for charged pollutants, electrostatic interactions and size exclusion effects jointly dominated the separation.

[0130] In addition, to systematically evaluate the multi-scenario application value of composite nanofiltration membranes, Figure 13b Two small-molecule odor compounds, 2-methylisoborneol (2-MIB) and geosmin (GSM), were also analyzed. The results showed that the TFC-O-P2 membrane exhibited superior removal efficiency for both 2-MIB and GSM. This is likely due to the strong size sieving, which makes it difficult for low-molecular-weight odor compounds to penetrate, while enhanced hydrophilicity and strong negative charge inhibit their adsorption and diffusion on the membrane surface. In summary, the synergistic effect of size sieving, electrostatic interaction, and antifouling performance enables the TFC-O-P2 membrane to achieve good removal efficiency for emerging pollutants and odor compounds.

[0131] Figure 14 evaluates the performance stability of nanofiltration membranes under changes in filtration pressure and salt concentration during long-term operation. Figure 14a In the study, the nanofiltration membrane flux increased approximately linearly as the filtration pressure increased from 1 bar to 6 bar, and the Na2SO4 rejection rate remained at a high level, indicating that the membrane has good pressure resistance stability. Figure 14b The results showed that as the Na2SO4 concentration increased from 1000 ppm to 5000 ppm, the water flux of the TFC-O-P2 membrane gradually decreased, while the salt rejection rate remained at a high level. This phenomenon was mainly due to the increased osmotic pressure and decreased effective driving pressure caused by the increase in feed concentration. Figure 14c The results showed that the permeability and Na2SO4 rejection rate of the TFC-O-P2 membrane remained stable during approximately 48 hours of long-term operation, indicating that the composite nanofiltration membrane has good long-term operational stability.

[0132] The antifouling properties of membranes can improve membrane lifespan and reduce membrane process operating costs. Figure 15 evaluates and compares the antifouling performance of TFC membranes and TFC-O-P2 membranes by filtering bovine serum albumin (BSA), salicylic acid (SA), and hyaluronic acid (HA) solutions. Figure 15aAs shown, in the three systems, the flux of both the TFC membrane and the TFC-O-P2 membrane remained relatively stable when using pure water as the feed. When the feed was switched to the target contaminant solution, the flux decreased; after washing and switching back to pure water, the flux recovered to a certain extent. In the BSA, SA, and HA contamination systems, the normalized flux decrease of the TFC-O-P2 membrane was less than that of the TFC membrane, indicating that the TFC-O-P2 membrane has better antifouling performance. This result is mainly attributed to the higher hydrophilicity, stronger negative charge, and more stable hydration layer of the TFC-O-P2 membrane, which helps reduce the adsorption of contaminants on the membrane surface.

[0133] In addition, to further analyze the membrane fouling process, flux recovery rate (FRR), total fouling rate (Rt), irreversible fouling rate (Rir), and reversible fouling rate (Rr) were calculated and compared, such as... Figure 15b As shown, compared to TFC membranes, TFC-O-P2 membranes exhibit improved flux recovery efficiency and reduced irreversible fouling rate, indicating that the TFC-O-P2 membrane modified with a porous hollow nanofiber interlayer has better antifouling performance. The improved flux recovery efficiency and pollutant removal capacity provide technical feasibility for long-term stable operation in practical water treatment scenarios.

[0134] The nanofiltration performance of the TFC-O-P2 membrane in this application, including water flux and salt rejection rate, such as... Figure 16 As shown, compared with other nanofiltration membranes, the TFC-O-P2 membrane exhibits superior overall performance, achieving a water flux of 28.52 L·m⁻²·h⁻¹·bar⁻¹ and a Na₂SO₄ rejection rate of 97.61%. This is attributed to the wrinkled polyamide morphology induced by the controlled interfacial polymerization process: the intermediate layer promotes the formation of wrinkled structures and thins the polyamide layer, thereby expanding the effective filtration area and reducing hydraulic resistance; simultaneously, the enhanced surface hydrophilicity helps accelerate water molecule transport.

[0135] It is evident that the composite nanofiltration membrane provided in this application exhibits excellent removal efficiency for emerging pollutants in water treatment. For example, the removal rates for small-molecule neutral hydrophobic pollutants methylparaben (MP), propylparaben (PP), benzylparaben (BP), and bisphenol A (BPA) are 37.47%, 41.34%, 97.03%, and 88.32%, respectively; and the removal rates for charged pollutants sulfamethoxazole (SMX) and trimethoprim (TMP) are 84.35% and 90.21%, respectively. In antifouling experiments, the flux recovery rates of the composite nanofiltration membrane after contamination with bovine serum albumin (BSA), salicylic acid (SA), and hyaluronic acid (HA) increased to 85.01%, 83.09%, and 90.24%, respectively. Under long-term operation, apart from slight fluctuations in flux, the rejection rate of Na2SO4 remains at a high level, indicating that the composite nanofiltration membrane of this application has good permeation performance, removal effect of emerging pollutants, anti-fouling performance and operational stability.

[0136] In fact, this embodiment only selects the preferred materials and preparation method for the composite nanofiltration membrane. In practical applications, a hydrophilic porous base membrane support layer is used, on which an oriented porous hollow nanofiber intermediate layer is formed. After interfacial polymerization, an ultrathin, highly cross-linked filter skin with a regular wrinkled structure is formed. Both can effectively shorten the water molecule transport path, reduce osmotic resistance, and thus increase water flux.

[0137] The foregoing has provided a detailed description of a composite nanofiltration membrane, its preparation method, and its applications. For those skilled in the art, appropriate adjustments can be made to the specific implementation methods and application scope without departing from the technical concept of this application; therefore, the content of this specification should not be construed as a limitation on the scope of protection of this application.

Claims

1. A composite nanofiltration membrane, characterized in that, The membrane comprises a porous base membrane support layer, an oriented porous hollow nanofiber intermediate layer, and a filter layer. The porous base membrane support layer is composed of a hydrophilic organic material. The oriented porous hollow nanofiber intermediate layer is loaded on the porous base membrane support layer. The filter layer is formed on the porous base membrane support layer loaded with the oriented porous hollow nanofiber intermediate layer. The nanofibers of the oriented porous hollow nanofiber intermediate layer have hollow cavities extending along the fiber axis and pore structures distributed on the surface of the fiber shell. The surface of the filter layer has a pleated structure along the fiber arrangement direction of the oriented porous hollow nanofiber intermediate layer.

2. The composite nanofiltration membrane as described in claim 1, characterized in that, The oriented porous hollow nanofiber intermediate layer is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer, and the pore structure is formed by removing the polyvinylpyrrolidone (PVP) component from the electrospinning shell solution.

3. The composite nanofiltration membrane as described in claim 1 or 2, characterized in that, The porous base membrane support layer is a polyethersulfone (PES) base membrane, and the filter layer is a polyamide (PA) layer.

4. The composite nanofiltration membrane as described in claim 3, characterized in that, The thickness of the polyamide layer is 45 nm to 70 nm.

5. A method for preparing a composite nanofiltration membrane, characterized in that, Includes the following steps: S1. Obtain a hydrophilic porous base membrane support layer; S2. An oriented porous hollow nanofiber intermediate layer is prepared by coaxial electrospinning and loaded onto the porous base film support layer to form a composite substrate. S3. An interfacial polymerization reaction is carried out on the composite substrate to form a polyamide filter layer.

6. The method for preparing the composite nanofiltration membrane as described in claim 5, characterized in that, The porous base membrane support layer obtained in step S1 is a polyethersulfone (PES) base membrane layer. The oriented porous hollow nanofiber intermediate layer prepared by coaxial electrospinning in step S2 is an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer. The composite substrate is formed by loading the oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer onto the polyethersulfone (PES) base membrane layer. The filter skin layer prepared in step S3 is a polyamide (PA) layer.

7. The method for preparing the composite nanofiltration membrane as described in claim 6, characterized in that, Step S2 includes: S21. Prepare an electrospinning shell solution and an electrospinning core solution; wherein the shell solution is prepared by a mixed solvent containing polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), N,N-dimethylformamide (DMF), and acetone, and the core solution is prepared by a mixed solvent containing polyvinylpyrrolidone (PVP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAc); S22. The electrospinning shell solution and the electrospinning core solution are spun simultaneously by coaxial electrospinning, and the spun composite substrate is subjected to ethanol immersion, water bath treatment and drying treatment to obtain an oriented porous hollow polyvinylidene fluoride (PVDF) nanofiber intermediate layer with hollow cavity and surface pore structure.

8. The method for preparing the composite nanofiltration membrane as described in claim 7, characterized in that, The shell solution is prepared by the following steps: polyvinylidene fluoride (PVDF) and polyvinylpyrrolidone (PVP) powders are completely dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and acetone to prepare an electrospinning shell solution; the core solution is prepared by the following steps: polyvinylpyrrolidone (PVP) powder is completely dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) to prepare an electrospinning core solution.

9. The method for preparing the composite nanofiltration membrane as described in claim 8, characterized in that, The method for preparing the electrospinning shell solution includes: dissolving 15% (w / v) polyvinylidene fluoride (PVDF) polymer and 5% to 20% (w / v) polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:1, completely dissolving at a constant temperature of 60°C, and allowing it to stand at 15°C to 25°C for degassing for more than 24 hours.

10. The method for preparing the composite nanofiltration membrane as described in claim 8, characterized in that, The preparation method of the electrospinning core layer solution includes: dissolving 30% by mass of polyvinylpyrrolidone (PVP) powder in a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethylacetamide (DMAc) in a volume ratio of 1:1, completely dissolving it under constant temperature conditions of 60°C, and letting it stand for more than 24 hours.

11. The method for preparing the composite nanofiltration membrane according to any one of claims 8 to 10, characterized in that, The coaxial electrospinning method is completed by an electrospinning device. Under the condition of collector rotation, the electrospinning time is set to 5 to 20 minutes, and the electrospinning shell solution and the electrospinning core solution are electrospinned simultaneously.

12. The method for preparing the composite nanofiltration membrane as described in claim 11, characterized in that, The conditions for coaxial electrospinning are as follows: an 18 kV voltage is applied, the relative humidity is maintained at 40% RH to 50% RH, the collector rotation speed is set to 700 rpm, the propulsion speed of the electrospinning shell solution is 2.0 mL / h, the propulsion speed of the electrospinning core solution is 1.5 mL / h, and the electrospinning duration is set to 10 minutes.

13. The method for preparing the composite nanofiltration membrane as described in claim 6, characterized in that, Step S3 includes: S31. The composite substrate is immersed in an aqueous solution containing a polyamine compound, and after a first specified time, excess aqueous solution is removed from the side of the composite substrate to which the filter layer is to be formed, to obtain a pretreated membrane. S32. Remove excess aqueous solution from the surface of the pretreated membrane and uniformly disperse the aqueous solution on the membrane surface; S33. Pour an organic phase solution containing polyacrylamide compounds onto the pretreated membrane and carry out an interfacial polymerization reaction. After a second specified time, remove the excess organic phase solution and dry and cure it to obtain a composite nanofiltration membrane with a polyamide (PA) layer.

14. The method for preparing the composite nanofiltration membrane as described in claim 13, characterized in that, Step S3 further includes the steps of preparing an aqueous phase solution and an organic phase solution, wherein the aqueous phase solution containing the polyamine compound is a piperazine (PIP) aqueous phase solution, and the organic phase solution containing the polyacrylamide compound is a 1,3,5-benzenetricarboxyl chloride (TMC) organic phase solution; the aqueous phase solution is a 0.5 wt% aqueous solution of piperazine (PIP), and the organic phase solution is a 0.1% (w / v) solution of 1,3,5-benzenetricarboxyl chloride (TMC).

15. The method for preparing the composite nanofiltration membrane as described in claim 14, characterized in that, The first specified time is 3 to 7 minutes, and the second specified time is 1 to 6 minutes; after the interface is polymerized, it is air-dried for 60 seconds and then cured in an oven for 5 minutes.

16. The use of the composite nanofiltration membrane according to claim 1 in filtering or retaining emerging pollutants, characterized in that, The emerging pollutants include at least one pollutant selected from methylparaben (MP), propylparaben (PP), benzylparaben (BP), bisphenol A (BPA), sulfamethoxazole (SMX), trimethoprim (TMP), 2-methylisoborneol (2-MIB), and geosmin (GSM).